IMPLEMENTASI MODEL FAN AND PICK DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI KERJA SAMA DI LINGKUNGANKU KELAS IV DI SEKOLAH DASAR - Maria Anita Bhibha; Moh. Farid Nurul Anwar; Muh. Fauzy Emqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
According to the actual conditions obtained by the data, some of the fourth grade students of SDN Merjosari 3 have not shown complete mastery of the material for each of their basic competencies, especially the field of Pancasila education study on cooperation on my environment. This is evidenced by the fact that there are still many student who have not reached the KKM. In this case, the Fan and Pick learning model is used as one of the learning models that can overcome this problem. This study uses the Classroom Action Research (CAR) type of research which has 2 cycles that have 4 stages, namely (1) initial planning, (2) implementation of actions, (3) observation, and (4) reflection. The results of observations of teacher teaching activities in cycle I and cycle II, in cycle I the observation results were 66,67% so that it was in the less category. In cycle II there was an increase, namely the observations results were 94,44% so that it was in the very good category. The results of observations of students learning avctivities in cycle I and cycle II, in cycle I the observation results were 66,67% with the less category. In cycle II there was an increase, namely the observation results were 88,89% so that it was in the good category. Student learning results in cycle I and cycle II, in cycle I only obtained 61,53% with the less category and in cycle II there was an in increase in learning results, namely obtaining 84,61% with the good category.